Enhanced and Tunable Surface Plasmons Assisted Emission from Reduced Graphene Oxide and Gold Hybrid Configuration - Junaid, M. (Institute of Electrical and Electronics Engineers Inc., 2021)
The reduced graphene oxide is expected to be material for enhanced plasmons emitter due to its unique optoelectronic properties. In this paper, we have performed FDTD analysis of reduced graphene oxide layer and on the hybrid gold structure and SiO2/Si substrate. Where remarkably enhanced and tunable plasmons emission from reduced graphene oxide was observed. In the prospective enhancement field emission from the simulation, the structure is conformed from FDTD analysis in term of absorption, reflectance, emission spectra. The tunable ability of emission radiation was also investigated with an induced energy bandgap in reduced graphene oxide. Moreover, the simulation results show that the reduced graphene oxide is suitable for optoelectronic device applications i.e., such as Fermi level modulations through low voltage implication. The structural design approach defined here will be very suitable for the forthcoming design of highly efficient optical and optoelectronic devices. In addition, the proposed design offers an alternative route for the application of reduced graphene oxide for optical and optoelectronic devices. Â© 2021 IEEE.